2016
DOI: 10.18001/trs.2.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking Outcomes in Tobacco Control Regulation and Communication: A Systematic Review

Abstract: Objective In this paper we synthesize the evidence from eye tracking research in tobacco control to inform tobacco regulatory strategies and tobacco communication campaigns. Methods We systematically searched 11 databases for studies that reported eye tracking outcomes in regards to tobacco regulation and communication. Two coders independently reviewed studies for inclusion and abstracted study characteristics and findings. Results Eighteen studies met full criteria for inclusion. Eye tracking studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 41 publications
3
52
0
Order By: Relevance
“…To our knowledge, this is the first study to examine the relationship between initial sensory attention toward health warnings and self-reported avoidance. Given the increasing volume of research using either eye-tracking or self-reported measures to assess warnings (8,10), our findings are important in indicating that contrary to some assumptions, these measurement tools are likely assessing different constructs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To our knowledge, this is the first study to examine the relationship between initial sensory attention toward health warnings and self-reported avoidance. Given the increasing volume of research using either eye-tracking or self-reported measures to assess warnings (8,10), our findings are important in indicating that contrary to some assumptions, these measurement tools are likely assessing different constructs.…”
Section: Discussionmentioning
confidence: 84%
“…There is considerable interest in using eye-tracking as an objective measure of attention to tobacco warnings (7)(8)(9)(10). Our previous research found that daily smokers but not occasional or non-smokers voluntarily shift their attention from warnings (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these theoretical models and research on warnings for cigarettes (Hammond et al, 2013;Meernik et al, 2016;Strasser, Tang, Romer, Jepson, & Cappella, 2012), we hypothesized that making warnings more visually prominent on e-cigarette advertisements by 1) increasing the amount of the advertisement surface they occupy (i.e., their size); and 2) changing their background color from white to red would increase attention to the warning message and recall of the message content and enhance effects on e-cigarette perceptions. Given the need for evidence of the effects of warning message regulations among tobacco users and non-users to support FDA tobacco regulations (Husten & Deyton, 2013), we also explored whether the effects of these e-cigarette warning label design features varied by cigarette smoking status and e-cigarette use.…”
Section: Introductionmentioning
confidence: 82%
“…Nor are we the first investigators to use the technique of eye tracking in the field of tobacco research. Others have used the technique to study which portions of the cigarette package individuals tend to focus on or avoid (Maynard et al 2014, Krugman et al 1994, Meernik et al 2016, Kessels and Ruiter 2012, Shankleman et al 2015, Munafo et al 2011, Strasser et al 2012. Our study follows a strand of research attempting to use the sequence of eye fixations -rather than simply the total number and duration of fixations -to elucidate information on search patterns (Russo and Rosen 1975).…”
Section: B What We Did Not Domentioning
confidence: 99%